2014
DOI: 10.1155/2014/789867
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Microstructure, and Mechanical Properties of Spinel-Corundum-Sialon Composite Materials from Waste Fly Ash and Aluminum Dross

Abstract: The solid wastes fly ash and aluminum dross were used to prepare the low cost, high added-value product spinel-corundum-Sialon with an in situ aluminothermic reduction-nitridation reaction. The effects of varying raw material components and heating temperatures on the phase compositions, microstructure, bulk density, apparent porosity, and bending strength of products were investigated. The presence of hazardous or impure elements in the products was also evaluated. The sintered materials mainly consisted of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The phase formation of b-Sialon whiskers were determined using X-ray diffraction (M21X-SRA, MAC Science Co. Ltd., Yokohama, Japan), scanning from 10 to 80 with a step of 0.02 (2) and a rate of 2 /min, and semi-quantitative analysis of the crystalline phase content were determined from the relative intensities of the diffraction peaks [24]. Scanning electron microscopy (ZJIESS CSM 950, Carl Zeiss Co., Oberkochen, Germany) equipped with an energy dispersive spectroscopy detector (EDS) was used to observed morphology and microstructure of the products.…”
Section: Characterization Of B-sialon Whiskersmentioning
confidence: 99%
See 2 more Smart Citations
“…The phase formation of b-Sialon whiskers were determined using X-ray diffraction (M21X-SRA, MAC Science Co. Ltd., Yokohama, Japan), scanning from 10 to 80 with a step of 0.02 (2) and a rate of 2 /min, and semi-quantitative analysis of the crystalline phase content were determined from the relative intensities of the diffraction peaks [24]. Scanning electron microscopy (ZJIESS CSM 950, Carl Zeiss Co., Oberkochen, Germany) equipped with an energy dispersive spectroscopy detector (EDS) was used to observed morphology and microstructure of the products.…”
Section: Characterization Of B-sialon Whiskersmentioning
confidence: 99%
“…7, with increasing sintering time, the surface of the samples started to melt. A melted catalyst droplet with the impurities (e.g., Fe, Mg, Ca, K, and Na) was formed under the influence of surface tension [9,24,34]. During heating, the Al 2 O 3 (s) and SiO 2 (s) containing in the fly ash would react with carbon to generate gaseous products, which may be SiO(g) and Al 2 O(g) according to the literature [9,13], and then these gases and N 2 (g) were dissolved into the liquid droplet ( Fig.…”
Section: Growth Mechanism Of B-sialon Whiskersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in the literature have reported the use of AD as a source of Al 2 O 3 . For instance, it has been employed in the manufacturing of calcium aluminate cement (Ünlü & Drouet, 2002) [7] and refractories (Ibarra Castro et al, 2009) [8] as well as in the production and synthesis of different composite materials (Ewais et al, 2009;Huang et al, 2014;Kim et al, 2009;Murayama et al, 2009;Yoshimura et al, 2008) [9][10][11][12][13]. AD has also been used as a substitute for cementitious material (Pereira et al, 2000) [14] and in the production of cellular concrete (Araújo & Tenório, 2005; Hwang & Song, 1997) [15,16], aluminous cement manufacturing (Ewais et al, 2009) [9], partial replacement of fine aggregate in mortars (Borhan & Janna, 2016;Llanos & Rodríguez, 2011;Pereira et al, 2000;Puertas et al, 1999) [14,[17][18][19], concrete block production (Shinzato & Hypolito, 2005) [20], and conventional concrete manufacturing (Elinwa & Mbadike, 2011;Mailar et al, 2016;Ozerkan et al, 2014;Reddy & Neeraja, 2016) [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were already focused upon the addition of various loadings of FA in clayey mixtures, for the production of conventional extruded or sintered ceramics or even composite materials, destined for construction applications [10][11][12][13][14][15]. At the same time, several studies reported the usage of FA for the production of advanced ceramics and composite materials [16,17].…”
Section: Introductionmentioning
confidence: 99%